Educational Characteristics in Medication Compliance Diabetes Mellitus in Indonesia - Amna, Faza Khilwan; Cahyati, Widya Hary (Journal of Creativity Student, 2025)
Background: Diabetes Mellitus (DM) is a chronic disease with a prevalence rate that continues to increase in Indonesia. Compliance with taking medication is a key factor in managing DM to prevent serious complications. However, the level of patient compliance with treatment is still a challenge. One factor that can increase compliance is education about the importance of DM therapy. Objective: This study aims to explore the characteristics of education about DM treatment that influence patient compliance in taking medication based on factors such as age, gender, education level, occupation, economic status, and place of residence in Indonesia. Method: This study used a descriptive analytical design with secondary data from the 2023 Indonesian Health Survey (SKI). The study sample included DM patients who were diagnosed and received drug therapy. The main variables analyzed were the proportion of patients who received education and their level of compliance in taking medication, which were categorized by age group, gender, education, occupation, economic status, and place of residence. Data analysis was carried out descriptively to identify the proportion of education in compliance with taking DM medication in Indonesia. Results: A study from the Indonesian Health Survey (SKI) showed that 81.4% of patients received education about the importance of taking medication regularly, and of that number, 90% showed high compliance in taking medication. Meanwhile, only 81% of patients who did not receive education remained compliant with their treatment. Conclusion: Education has been shown to have a significant relationship with adherence to taking DM medication in Indonesia. Patients who receive education have a higher level of adherence than those who do not receive education. Age, education, occupation, and economic status factors play a role in determining the level of patient adherence. The results of this study can be the basis for designing education-based interventions to improve adherence to DM therapy in Indonesia.